2012
DOI: 10.1016/j.pnpbp.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation impairs emotional memory retrieval in mice: Influence of sex

Abstract: The deleterious effects of paradoxical sleep deprivation on memory processes are well documented. However, non-selective sleep deprivation occurs more commonly in modern society and thus represents a better translational model. We have recently reported that acute total sleep deprivation (TSD) for 6 h immediately before testing impaired performance of male mice in the plus-maze discriminative avoidance task (PM-DAT) and in the passive avoidance task (PAT). In order to extend these findings to females, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 55 publications
(69 reference statements)
1
24
0
Order By: Relevance
“…In these cases, more than reviewing the effects of lack of sleep on anxiety, we were reviewing the consistency of some research groups' works. Such was the case for the staircase test, used only by Dr. Pokk's group (Pokk and Väli, 2001a, b;Vassiljev et al, 2000), plus-maze discriminative avoidance task, used only by Dr. Frussa-Filho's group (Alvarenga et al, 2008;Fernandes-Santos et al, 2012;Patti et al, 2010;Silva et al, 2004a;Takatsu-Coleman et al, 2013), and for the mirror chamber test and the zero maze, exclusively used by Dr. Kumar's group Kumar and Garg, 2008;Kumar and Singh, 2007, 2008Singh and Kumar, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, more than reviewing the effects of lack of sleep on anxiety, we were reviewing the consistency of some research groups' works. Such was the case for the staircase test, used only by Dr. Pokk's group (Pokk and Väli, 2001a, b;Vassiljev et al, 2000), plus-maze discriminative avoidance task, used only by Dr. Frussa-Filho's group (Alvarenga et al, 2008;Fernandes-Santos et al, 2012;Patti et al, 2010;Silva et al, 2004a;Takatsu-Coleman et al, 2013), and for the mirror chamber test and the zero maze, exclusively used by Dr. Kumar's group Kumar and Garg, 2008;Kumar and Singh, 2007, 2008Singh and Kumar, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 50 articles composed our sample (Alvarenga et al, 2008;Andersen et al, 2005;Araujo et al, 2006;Berro et al, 2014;Cohen et al, 2012;Cortese et al, 2010;de Oliveira et al, 2004;Dubiela et al, 2011;Fernandes-Santos et al, 2012;Garg and Kumar, 2008;Hajali et al, 2012;Kalonia and Kumar, 2007;Kumar and Garg, 2008;Kumar and Kalonia, 2007;Kumar and Singh, 2007, 2008Nair et al, 2011;Novati et al, 2011;Patti et al, 2010;Perry et al, 2008;Pires et al, 2013;Pokk et al, 1996;Pokk et al, 2000;Väli, 2001a, b, 2002;Pokk and Zharkovsky, 1995, 1997, 1998aPolesel et al, 2014;Porsolt et al, 1978;Rothman et al, 2013;Silva et al, 2004a;Silva et al, 2004b;Singh and Kumar, 2008;Singh et al, 2013;Suchecki et al, 2002;Süer et al, 2011;Takatsu-Coleman et al, 2013;Tartar et al, 2009;Torabi-Namia et al, 2012;Vassiljev et al, 2000;Vollert et al, 2011a;…”
Section: Selected Studies and Sample Descriptionmentioning
confidence: 99%
“…Several studies in laboratory rats have shown that extended (REM) sleep deprivation for 1-4 days prior to acquisition impairs subsequent encoding and/or formation of contextual fear memories (McDermott et al 2003;Ruskin et al 2004;Chen et al 2006;Tiba et al 2008;Fernandes-Santos et al 2012). In one study, prolonged sleep deprivation had no effect on the acquisition of tone-cued fear conditioning (Ruskin et al 2006).…”
Section: Sleep and Fear Memoriesmentioning
confidence: 99%
“…Animals that experienced SD indicated significant cognitive impairments in various paradigms such as radial ram water maze (16), Morris water maze (MWM) (6,17,19), and the plus-maze discriminative avoidance task (39). The negative effects of SD on emotional memory of mice were previously recognized (8). The ability of mice to retain novel information and consolidate memory was interrupted by SD (40).…”
Section: Sleep Deprivation and Cognitive Disordersmentioning
confidence: 99%
“…It seems that sleep is the main factor in the acquisition and consolidation of memory (4,5). Therefore, sleep deprivation (SD) impairs spatial (6,7), emotional (8), and working memories (9), and augments anxiety like behaviors (10). As a result, hippocampus is very sensitive to sleep loss (11,12).…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%